TEACHING SPEAKING NARRATIVE TEXT BY USING PREZI TO JUNIOR HIGH SCHOOL STUDENTS - Try Willyam Ningsih; Fitrawati Fitrawati (Universitas Negeri Padang, 2018)
The aim of this paper is to explain the use of Prezi in teaching speaking at junior high school. Prezi is one of the media that can be used by the teacher in teaching and learning process, especially in Narrative Text. Using Prezi in class is very good in order to make students more interested in talking in front of the class. Prezi is a good media as it can add pictures, musics, and videos. There are some steps in teaching speaking by using Prezi. First, the teacher makes a Prezi presentation before coming to the class. Second, the teacher shows the Prezi presentation about Narrative Text to the students. Third, the teacher asks students to retell the story that they already seen by using Prezi. Fourth, the teacher asks students to practice speaking in groups. Fifth, the teacher asks students to tell the story that they have been practicing by using Prezi in front of the class. Last, Teacher and students conclude the lesson together. By using Prezi in the classroom, it will be easier for the students to speak infront of the class because there are pictures and sentences that help students to tell the story.